The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5120/ijca2016910595
|View full text |Cite
|
Sign up to set email alerts
|

Study and Analysis of Breast Cancer Cell Detection using Naïve Bayes, SVM and Ensemble Algorithms

Abstract: Breast cancer is one of the second leading causes of cancerdeath in women. Despite the fact that cancer is preventable and curable in primary stages, the huge number of patients are diagnosed with cancer very late. Conventional methods of detecting and diagnosing cancer mainly depend on skilled physicians, with the help of medical imaging, to detect certain symptoms that usually appear in the later stages of cancer [1]. The objective of this paper is to find the smallest subset of features that can ensure high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Naïve Bayesian (NB) classifier relies on applying Bayes" theorem to estimate the most probable membership of a given event in one of a set of possible classes. It is described as being naïve, since it assumes independence among variables used in the classification process [15], [17], [18].…”
Section: Naïve Bayesian Classifiermentioning
confidence: 99%
See 1 more Smart Citation
“…Naïve Bayesian (NB) classifier relies on applying Bayes" theorem to estimate the most probable membership of a given event in one of a set of possible classes. It is described as being naïve, since it assumes independence among variables used in the classification process [15], [17], [18].…”
Section: Naïve Bayesian Classifiermentioning
confidence: 99%
“…Consider the duality problem in Soft Margin SVM for nearly linearly differentiated data: (18) Inside: N: number of data point pairs in training set.…”
Section: Support Vector Machinementioning
confidence: 99%
“…Most of the research papers that have published on the predictive model for breast cancer have shown relatively high prediction accuracies [7], [8], [21]. However, a widespread problem in medical data is a class imbalance, which was failed to be addressed by any of these previous papers.…”
Section: Related Workmentioning
confidence: 99%
“…The comparative study on different classifiers namely, Naï ve Bayes, SVM, and ensemble classifiers were implemented on the processed dataset. Naï ve Bayes yields the optimum accuracy of 97.39% on classifying the breast cancer with time complexity of 0.1020 milliseconds [11]. Further, study have shown improvement using the Sequential Minimal Optimization (SMO) to overcome the quadratic programming problem arises during the SVM training [12].…”
Section: A Wbc Datasetsmentioning
confidence: 99%